Effects of rosa mosqueta oil supplementation in lipogenic markers associated with prevention of liver steatosis. Issue 2 (27th January 2017) - Dossi, Camila G.; Cadagan, Cynthia; San Martín, Marcela; Espinosa, Alejandra; González-Mañán, Daniel; Silva, David; Mancilla, Rodrigo A.; Tapia, Gladys S.
Abstract : Rosa mosqueta (RM) oil is rich in α-linolenic acid (ALA) – a precursor of eicosapentaenoic (EPA) and docosahexaenoic acid (DHA), and it has a high antioxidant activity due to its abundant content of tocopherols. Abstract : Rosa mosqueta (RM) oil is rich in α-linolenic acid (ALA) – a precursor of eicosapentaenoic (EPA) and docosahexaenoic acid (DHA), and it has a high antioxidant activity due to its abundant content of tocopherols. Additionally, it has been observed that RM oil administration prevents hepatic steatosis. Thus, the aim of this study was to demonstrate the antilipogenic mechanism related to RM oil administration in a high-fat diet (HFD) fed mice model by evaluating markers associated with the regulation of lipid droplet metabolism (PLIN2, PLIN5 and PPAR-γ), and proteins associated with lipogenesis (FAS and SREBP-1c). C57BL/6J mice were fed either a control diet or a HFD, with and without RM oil supplementation for 12 weeks. The results showed that RM oil supplementation decreases hepatic PLIN2 and PPAR-γ mRNA expression and SREBP-1c, FAS and PLIN2 protein levels, whereas we did not find changes in the level of PLIN5 among the groups. These results suggest that modulation of lipogenic markers could be one of the mechanisms, through which RM oil supplementation prevents the hepatic steatosis induced by HFD consumption in a mice model.